THE EFFECT OF HALAL CERTIFICATION AND CELEBRITY ENDORSEMENT TOWARD PURCHASE INTENTION WITH BRAND IMAGE AS MEDIATING ROLE (EMPIRICAL STUDY OF WARDAH PRODUCT IN PONTIANAK) - Nisa, Dheliz Fahratun B1024161017 (Jurnal Manajemen Update, 2020)
The purpose of this research is to analyzed the effect of Halal Certification and Celebrity Endorsement toward Purchase Intention with Brand Image as mediating role toward halal product issues rapidly increase. These day, Muslim consumer has been increase and aware to use halal product to fulfill their obligations. A Muslim in the consumption of goods or services must not only put forward the use value of goods or services, but also consider the benefits of consuming goods or services. This survey research that conducted to understand the causal relationship among variable using questionnaire as the instrument for gather the data. The questionnaire distributed to 100 sample to fulfill the requirements. The sample for this research is come from Pontianak people who are on age 15 years old till 40 years old or above that use halal cosmetic. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis use PLS method, this research use WarpPLS 4.0 software. The hypothesis of the research is H1: Halal certification has positive influence to brand image of wardah product in Pontianak, H2: Halal certification has positive influence to purchase intention of wardah product in Pontianak, H3: Celebrity endorsement has positive influence to brand image of wardah in Pontianak, H4: Celebrity endorsement has positive influence to purchase intention of wardah product in Pontianak, H5 : Brand image has positive influence to purchase intention of wardah product in Pontianak. There is significant relationship between variable. The result of this research shows that H1, H2, H3, H4, and H5 are accepted.Â Keyword: halal certification, celebrity endorsement, brand image, purchase intention.Â REFERENCESÂ A Shimp, Terence. (2007). Â â€œPeriklanan Promosi ( Aspek Tambahan KomunikasiPemasaran Terpadu)â€. Jilid I, edisi Terjemahan, Jakarta : Erlangga.Â Aaker, D. A., & Keller, K. L. (1990). Consumer evaluations of brand extensions.Journal of Marketing, 54(1), 27-41.Â Aaker, D.A. (1996), â€œMeasuring brand equity across products and marketsâ€,California Management Review, Vol. 38 No. 3, pp. 102-120.Â Aaker, David, A. dan Alexander, L. Biel, 2009, Brand Equity and Advertising:Advertising Role in Building Strong Brand, Lawrence Erlbaum Associates, Inc.,Â Ajzen, I. (1985). From intentions to actions: A Theory of Planned Behavior. In J.Kuhl & J. Beckman (Eds.), Action-control: From Cognition to Behavior (pp. 11-39).Â Annabi, C. and Ibidapo-Obe, O. (2017), â€œHalal certification organizations in theUnited Kingdomâ€, Journal of Islamic Marketing, Vol. 8 No. 1, pp. 107-126.Â Approach. Journal of International Food & Agribusiness Marketing, Vol. 25(1): 23. Research Review, Vol. 38(6).Â Apriyantono, A. Hermanianto, J. and Wahid N. (2007). Pedoman Produksi Pangan Halal. Jakarta (ID): Khairul Bayan Press.Â Assael, H., (2001). Consumer Behavior 6th Edition. New York: Thomson Learning.Â Atkin, C., & Block, M. (1983). Effectiveness of Celebrity Endorsers. Journal of Advertising Research, 23(1), 57-61.Â Atkin, C., Hocking, J., & Block, M. (1984). Teenage Drinking: Does AdvertisingMake a Difference. Journal of Communication, 34(2), 157-167.Â Awan, H.M. Siddiquei, A.N. and Haider, Z. (2015). Factors Affecting HalalPurchase Intention â€“ Evidence from Pakistanâ€™s Halal Food Sector. ManagementÂ Aziz, Y.A. and Chok, N.V. (2013). The Role of Halal Awareness, HalalCertification, and Marketing Components in Determining Halal Purchase Intention Among Non-Muslims in Malaysia: A Structural Equation Modeling. Article in Journal of International Food & Agribusiness Marketing.Â Beneke, J., de Sousa, S., Mbuyu, M. and Wickham, B. (2016), â€œThe effect ofnegative online customer reviews on brand equity and purchase intention of consumer electronics in South Africaâ€, The International Review of Retail, Distribution and Consumer Research, Vol. 26 No. 2, pp. 171-201.Â Bimal Anjum, Dr, Sukhwinder Kaur Dhanda and Sumeet Nagra, 2012. Impact ofCelebrity Endorsed Advertisiments on Consumers. Asia Pacific Journal of Marketing & Management Review. 1 (2): h: 22-33Â Bower, A. B., & Landreth, S. (2001). Is Beauty Best? Highly Versus NormallyAttractive Models in Advertising. Journal of Advertising, 30(1), 1-12.Â Das, S., & Padhy, P. K. (2012). Brand Perception (Aaker, 1996)by CelebrityEndorsement. International Journal of Advanced Research in Management and Social Sciences, 1(2), 79-93.Â E.Stevens, R. (2006). The Marketing Research Guide. Routledge.Â Erdogan, B. Z. (1999). Celebrity Endorsement: A Literature Review. Journal of Marketing Management, 15(4), 291-314.Â Erdogan, Z. B., Taggs, S., & Baker, M. J. (2001). Selecting Celebrity Endorsers:The Practitionerâ€™s Perspective. Journal of Advertising Research, 41(3), 39-48.Â Fink, A. (2003). The survey handbook. 2nd ed. Thousand Oaks, California: SagePublications, Inc.Â Friedman, H. H. & Friedman, L. (1979). Endorser effectiveness by product type.Journal of Advertising Research, 19(5), 63-71.Â Ghazali, I. (2008). Structural Equation Modeling Metode Alternatif dengan PartialLeast Square. Semarang: Badan Penerbit Universitas Diponogoro.Â Ghozali, Imam, 2013. Aplikasi Analisis Multivariat dengan Program IBM SPSS21. Edisi 7, Penerbit Universitas Diponegoro, Semarang.Â Hair, J.F., Black, W.C., Babin, B.J. and Anderson, R.E. (2010), Multivariate DataAnalysis, Prentice Hall, Upper Saddle River, NJ.Â Hovland, C., Janis, L., & Kelley, H. (1953). Communication and Persuasion. NewHaven, CT: Yale University Press.Â Issa, Z.M. et al. (2009). Practices of Food Producers in Producing Halal Food.Interdisciplinary Journal of Conpemporary Research in Business, Vol. 1(7).Â Kelman, H. C. (1961). Process of Opinion Change. Public Opinion Quarterly 25(1),57-78.Â Kotler, Philip, dan Amstrong, Gary, 2001, Prinsip-Prinsip Manajemen, Jilid I, Edisi Ke Delapan, Alih Bahasa Oleh Damos Sihombing, MBA., Erlangga, Jakarta.Â Kotler, P. and Keller, K.L. (2009). Manajemen Pemasaran Edisi 13 Jilid 1. Jakarta(ID): Penerbit Erlangga.Â Kuncoro, Mudrajad. (2009). Metode Riset Untuk Bisnis Dan Ekonomi. Jakarta:Gelora Aksara Pratama.Â Lin, N & Lin, B. 2007. The Effect of Brand Image and Product Knowledge onPurchase Intention Moderated by Price Discount. Journal of InternationalManagement Studies.Â Munnukka, Juha, Outi Uusitalo, and Hanna Toivonen (2016), "Credibility of a PeerEndorser and Advertising Effectiveness," Journal of Consumer Marketing 33 (3), 182-192.Â McCracken, G. (1989), "Who is the Celebrity Endorser? Cultural Foundation of theEndorsement Process", Journal of Consumer Research, 16, (December), pp. 310-321.Â Netemeyer, R. et. al, (2003). Scaling Procedures: Issues and Applications. SAGE.Â Ohanian, R. (1990). Construction and Validation of a Scale to Measure CelebrityEndorserâ€™s Perceived Expertise, Trustworthiness and Attractiveness. Journal of Advertising, 19(3), 39-52.Â Palmer, Adrian. 2001. Principles of Services Marketing, Third Edition McGraw-Hill Companies, UK (United Kingdom)Â Pradhan, Debasis, Israel Duraipandian, and Dhruv Sethi (2016), "CelebrityEndorsement: How Celebrityâ€“Brandâ€“User Personality Congruence Affects Brand Attitude and Purchase Intention," Journal of Marketing Communications 22 (5), 456-473.Â Riaz, M.N. and Chaudry, M.M. (2004), Halal Food Production, CRC Press, BocaRaton, FL.Â Schiffman, Leon, & Kanuk, Leslie Lazar. 2007. Consumer Behaviour 7 th.Edition. (Perilaku Konsumen). Jakarta: PT. IndeksÂ Â Sekaran, U., and Bougie, R. 2009. Research Methodes for Business, A skillbuilding approach. Fifth Edition. WileyÂ Shah.S.H.S.J ., Jaffari,R,A., Ejaz Wasiq., Fatima M & Sherazi K,S . 2011., TheImpact Of Brands On Consumer Purchase Intentions, J.Marketing. Www.Nzta. Govr.Nz/Resources/Perceptions (Accessed on November 6, 2015)Hillsdale.Â Shaari, Jamal A.N. & Arifin, NS (2010). Dimension of Halal Purchase Intention: APreliminary Study.Â Sorenson, H.T., Sabroe, S., & Olsen, J. (1996). A framework for evaluation ofsecondary data sources for epidemiological research. International Journal of Epidemiology, 25 (2), 435-442.Â Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&B. Bandung:AlfabetaÂ Sugiyono. 2013. Metode Penelitian Kuantitatif Kualitatif dan R & D. Bandung:Alfabeta.Â Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kuantitatif,Kualitatif, dan R&D. Bandung: Alfabeta.Â Windikusuma, Dewi Kirana.(2015). Pengaruh Kesadaran Halal Terhadap Sikapdan Implikasinya Terhadap Minat Beli Ulang. Thesis, Faculty of Economicsand Business, Diponegoro University, Semarang.Â Wu, J.H., Wu, C.W., Lee, C.T. and Lee, H.J. (2015), â€œGreen purchase intentions:an exploratory study of the Taiwanese electric motorcycle marketâ€, Journal of Business Research, Vol. 68 No. 4, pp. 829-833.Â Zhou, Lianxi, and Paul Whitla (2013), "How Negative Celebrity PublicityInfluences Consumer Attitudes: The Mediating Role of Moral Reputation," Journal of Business Research 66 (8), 1013-1020.